Collaboration by the public sector: findings by watchdogs in Australia and New Zealand. Issue 3 (16th April 2017) - Wilkins, Peter; Phillimore, John; Gilchrist, David
Abstract : Drawing on an analysis of 112 watchdog reports that addressed collaboration, this paper concludes that governance issues make up a large proportion of all issues identified. Less commonly found were specific references to capacity and information management as important elements for effective collaboration. The evidence from watchdog reports confirms that collaboration remains very problematic for the public sector. Moreover, it is not evident that the wider public sector is drawing on this evidence extensively to learn and improve.